IMPLEMENTATION OF SAJADAH SAVINGS (WADIAH TERM DEPOSIT) TO IMPROVE MEMBER WELFARE AT BMT NU (NUANSA UMAT) GENTENG BRANCH - Hoirul Ma’muli; Nawal Eka Susanti (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the role of optimizing Islamic savings in Baitul Maal wat Tamwil Nuansa Umat (BMT NU) in improving the welfare of the Muslim community in the Genteng area. Using a qualitative approach with a case study method, this research examines how the management and implementation of Sharia principles in savings products at BMT NU contribute to the economic well-being of the community. The focus of this study is to understand the extent to which the use of Islamic savings can positively impact access to financial services and local economic development. The results show that the optimization of Islamic savings based on the principles of profit-sharing, trustworthiness, and transparency encourages greater participation from the community in Sharia-based economic activities, potentially improving their welfare. These findings are expected to serve as a foundation for BMT and other Islamic financial institutions in developing more effective programs to support the economic growth of the Muslim community.